2008
DOI: 10.1007/s10886-008-9509-0
|View full text |Cite
|
Sign up to set email alerts
|

Active Space of Pheromone Plume and its Relationship to Effective Attraction Radius in Applied Models

Abstract: The release rate of a semiochemical lure that attracts flying insects has a specific effective attraction radius (EAR) that corresponds to the lure's orientation response strength. EAR is defined as the radius of a passive sphere that intercepts the same number of insects as a semiochemical-baited trap. It is estimated by calculating the ratio of trap catches in the field in baited and unbaited traps and the interception area of the unbaited trap. EAR serves as a standardized method for comparing the attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 60 publications
(63 reference statements)
1
49
0
Order By: Relevance
“…Currently, there are no methods and equations that use trap catch data to estimate insect flight densities, a crucial factor in the success of mass trapping and mating disruption programs (Shorey, 1977;Cardé, 1990;Cardé and Minks, 1995;Miller et al, 2006a, b;El-Sayed et al, 2006, 2009Byers, 2007Byers, , 2008. In order to develop methods and equations for determining flight densities from trap catch data, several parameters need to be estimated and understood.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, there are no methods and equations that use trap catch data to estimate insect flight densities, a crucial factor in the success of mass trapping and mating disruption programs (Shorey, 1977;Cardé, 1990;Cardé and Minks, 1995;Miller et al, 2006a, b;El-Sayed et al, 2006, 2009Byers, 2007Byers, , 2008. In order to develop methods and equations for determining flight densities from trap catch data, several parameters need to be estimated and understood.…”
Section: Introductionmentioning
confidence: 99%
“…In mass trapping for control of insects, the most effective lure is that with the largest EAR ascertained by field-testing the semiochemical at increasing release rates. The EAR has been used in simulation models of mass trapping and mating disruption (Byers, 2007) that are important tools of integrated pest management (Shorey, 1977;Cardé, 1990;Cardé and Minks, 1995;Miller et al, 2006a, b;El-Sayed et al, 2006, 2009Byers, 2008). These and other studies, however, have relied upon subjectively testing densities of lures/traps by trial and error until some negative effect on mating success was observed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations